Remaking the Technosubject: Kenyan Men Contextualizing HIV Self-Testing Technologies. Issue 3 (3rd April 2022) - Thomann, Matthew; Kombo, Bernadette; Musyoki, Helgar; Masinya, Kennedy; Kuria, Samuel; Kyana, Martin; Musimbi, Janet; Lazarus, Lisa; Blanchard, James; Bhattacharjee, Parinita; Lorway, Robert
ABSTRACT: The Kenyan government offers free HIV self-testing kits to men who have sex with men. The value of self-testing is based on the imaginary of an autonomous technosubject empowered to independently control testing services, thereby "freed, " through technology, from the social conditions that might inhibit health services utilization. Following a community-centered collaborative approach, community researchers interviewed their peers who examined and reacted to the technology. Participants reframed the technosubject as intertwined with the social world and the testing kit itself as an object that exerts agency and possesses affective potential. Attending to these socio-material relationalities offers insights into program planning.